2020
DOI: 10.1186/s12967-020-02338-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IL-19, -20, and -24 in acute and chronic kidney diseases reveals a pro-fibrotic role of IL-24

Abstract: Background: Recently, the role of IL-19, IL-20 and IL-24 has been reported in renal disorders. However, still little is known about their biological role. Methods: Localization of IL-20RB was determined in human biopsies and in the kidneys of mice that underwent unilateral ureteral obstruction (UUO). Renal Il19, Il20 and Il24 expression was determined in ischemia/reperfusion, lipopolysaccharide, streptozotocin, or UUO induced animal models of kidney diseases. The effects of H 2 O 2 , LPS, TGF-β1, PDGF-B and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
4
16
1
Order By: Relevance
“…7 ). These results are in accordance with our previous study demonstrating decreased ECM deposition in the kidney of Il20rb KO mice underwent unilateral ureteral obstruction compared to that of WT animals [ 18 ]. Taken together our above in vivo experiment demonstrate that IL-20 cytokines have strong and multiple effects on tissue remodeling of the inflamed colon.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…7 ). These results are in accordance with our previous study demonstrating decreased ECM deposition in the kidney of Il20rb KO mice underwent unilateral ureteral obstruction compared to that of WT animals [ 18 ]. Taken together our above in vivo experiment demonstrate that IL-20 cytokines have strong and multiple effects on tissue remodeling of the inflamed colon.…”
Section: Discussionsupporting
confidence: 93%
“…1 ). Indeed, similarly to recent studies [ 19 ] we found that IL-1ß acts as an inducer of IL-24 synthesis, however our data, in line with our previous results [ 18 ] demonstrated that LPS or H 2 O 2 treatment has similar or even stronger effect on IL-24 synthesis in PBMCs and LPMCs. These data fit well into the literature suggesting the regulatory effect of LPS and IL-1ß on the IL-24 synthesis of immune cells [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It can also increase the expression of TGF, TNF, and Col1 and promotes the proliferation and migration of activated HSCs [21]. In psoriasis, IL-20 stimulates monocytes to produce pro-in ammatory cytokines and indirectly exerts its effect on keratinocyte proliferation through immune cells in the skin [22].In renal brosis disease, the pro-brotic effects of IL-19, IL-22, and IL-24 on the kidney was con rmed in a mouse renal disease model [23]. As a crucial member of the IL-20 subfamily, IL-19 has been found to be highly expressed in many chronic in ammatory diseases, such as psoriasis and asthma.…”
Section: Introductionmentioning
confidence: 99%